2011
DOI: 10.1177/0267658310382068
|View full text |Cite
|
Sign up to set email alerts
|

Adding more fuel to the fire: An eye-tracking study of idiom processing by native and non-native speakers

Abstract: Using eye-tracking, we investigate on-line processing of idioms in a biasing story context by native and non-native speakers of English. The stimuli are idioms used figuratively (at the end of the day -'eventually'), literally (at the end of the day -'in the evening'), and novel phrases (at the end of the war). Native speaker results indicate a processing advantage for idioms over novel phrases, as evidenced by fewer and shorter fixations. Further, no processing advantage is found for figurative idiom uses ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
266
7
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(314 citation statements)
references
References 41 publications
38
266
7
3
Order By: Relevance
“…Siyanova-Chanturia et al (2011) corroborated the processing advantages of idioms over novel phrases and showed that idioms required less re-reading and less re-analysis. Interestingly, there were no significant differences in the early gaze measures, suggesting that early eye-tracking measures may not be suitable for investigation of formulaic language (Siyanova-Chanturia et al, 2011). This result may be explained with previous research on predictability of single words showing strong effects in terms of shorter first fixation durations and greater likelihood of skipping (Rayner and Well, 1996).…”
Section: Eye Tracking and Formulaic Languagementioning
confidence: 64%
“…Siyanova-Chanturia et al (2011) corroborated the processing advantages of idioms over novel phrases and showed that idioms required less re-reading and less re-analysis. Interestingly, there were no significant differences in the early gaze measures, suggesting that early eye-tracking measures may not be suitable for investigation of formulaic language (Siyanova-Chanturia et al, 2011). This result may be explained with previous research on predictability of single words showing strong effects in terms of shorter first fixation durations and greater likelihood of skipping (Rayner and Well, 1996).…”
Section: Eye Tracking and Formulaic Languagementioning
confidence: 64%
“…Eye-tracking methodology has been used to investigate several phenomena in L1 and L2 reading, such as sentence processing (e.g., Altarriba, Kroll, Scholl, & Rayner, 1996 ), the processing of formulaic language (e.g., Siyanova-Chanturia, Conklin, & Schmitt, 2011 ), and noticing of corrective feedback (e.g., Smith, 2012 ). However, only a few studies have used eye-tracking methodology to investigate the process of vocabulary learning from reading.…”
Section: Eye Movements In Vocabulary Acquisition Researchmentioning
confidence: 99%
“…Findings suggest that idioms are processed faster than phrases, across several measures including response times in a phrase classification task (Swinney & Cutler, 1979), self-paced reading times (Conklin & Schmitt, 2008), and fixation times on final words (Underwood, Schmitt, & Galpin, 2004) and across the whole idioms (Siyanova-Chanturia, Conklin, & Schmitt, 2011).…”
Section: More Recently Cutter Drieghe and Liversedge (2014) Demonstmentioning
confidence: 99%